De herkomst van vertrouwen in de rechtsstaat 1993 - 2012 onderzocht via tekstmining van de mediaberichtgeving en analyse van de publieke opinie - Kleinnijenhuis, Jan (Vrije Universiteit Amsterdam, 2012)
Issues that touch on the separation of powers, that is, on the relationship between parliament, government and the judiciary, and on the relationship between the Public Prosecution Service, the legal profession and the judge, have been rife in the news of the past twenty years ( for example IRT affair, acquittal of terror suspects, trial Wilders). The separation of powers is part of most Dutch definitions of the rule of law. The research resulting from this WODC publication is aimed at identifying trends and patterns in messages (from newspapers, television news bulletins, news websites, Twitter) over the past twenty years that could affect confidence in the rule of law. It was examined whether text mining, that is, automated text analysis or "content analysis", is an appropriate research tool.